EMPLOYEE WELFARE AND ACCOUNTABILITY - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
According to (Balfour 2013), “Employee welfare refers to the efforts made by the employers to improve the working and living conditions over and above the wages paid to them. In its widest sense it comprises all matters affecting the health, safety, comfort and general welfare of the workmen, and includes provision for education, recreation, thrift schemes, convalescent homes”. It covers almost fields of activities of workers e.g., social, economic, industrial and educational. According to (N.M. Joshi, 2011) “Employee welfare work covers all the efforts which employers take for the benefit of their employees over and above the minimum standards of working conditions fixed by the Factories Act and over and above the provisions of the social legislation providing against accident, old age, unemployment and sickness”.